Agricultural diversification a sense of urgency - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Regional conference on Agriculture Diversification and this was held in collaboration with CARDI (Caribbean Agricultural Research and Development Institute) in Bridgetown, Barbados from November 27 to December 1,1989